Emerging Threats to Animals in the United Kingdom by Arthropod-Borne Diseases - Folly, Arran J.; Dorey-Robinson, Daniel; Hernández-Triana, Luis M.; Phipps, L. Paul; Johnson, Nicholas (Frontiers in Veterinary Science, 2020)
Worldwide, arthropod-borne disease transmission represents one of the greatest threats to public and animal health. For the British Isles, an island group on the north-western coast of continental Europe consisting of the United Kingdom (UK) and the Republic of Ireland, physical separation offers a barrier to the introduction of many of the pathogens that affect animals on the rest of the continent. Added to this are strict biosecurity rules at ports of entry and the depauperate vector biodiversity found on the islands. Nevertheless, there are some indigenous arthropod-borne pathogens that cause sporadic outbreaks such as the tick-borne louping ill virus, found almost exclusively in the British Isles, and a range of piroplasmid infections that are poorly characterised. These provide an ongoing source of infection whose emergence can be unpredictable. In addition, the risk remains for future introductions of both exotic vectors and the pathogens they harbour, and can transmit. Current factors that are driving the increases of both disease transmission and the risk of emergence include marked changes to the climate in the British Isles that have increased summer and winter temperatures, and extended the period over which arthropods are active. There have also been dramatic increases in the distribution of mosquito-borne diseases such as West Nile and Usutu viruses in mainland Europe that are making the introduction of these pathogens through bird migration increasingly feasible. In addition, the establishment of midge-borne bluetongue virus in the near continent has increased the risk of wind-borne introduction of infected midges and the inadvertent importation of infected cattle. Arguably the greatest risk is associated with the continual increase in the movement of people, pets and trade into the UK. This, in particular, is driving the introduction of invasive arthropod species that either bring disease-causing pathogens, or are known competent vectors, that increase the risk of disease transmission if introduced. The following review documents the current pathogen threats to animals transmitted by mosquitoes, ticks and midges. This includes both indigenous and exotic pathogens to the UK. In the case of exotic pathogens, the pathway and risk of introduction are also discussed.